Macroeconomic Impact of the Itaipu Treaty Review for Paraguay - Che, Natasha (IMF Working Papers; Working Paper, 2021)
With the debt obligation of Itaipu Binational being completed paid off by 2023, the Annex C of the Treaty of Itaipu, which governs the operation and revenue distribution of the Itaipu Dam, is due for review and possible revisions. The implications for Paraguay's export revenues and fiscal position are potentially significant. The paper reviews the current energy distribution and sales arrangements of Itaipu and the potential implication of the Annex C revision for the future.